An analysis of relative clauses in scientific sentences - Jikti Khairina; Mulyadi, Mulyadi (Indonesian Research Journal in Education |IRJE|, 2025)
This research examines the application of restrictive and non-restrictive relative clauses in academic journal articles, focusing on their syntactic and functional significance within linguistic discourse. This study utilizes data from the research titled “Verbal Humor in Selected Indonesian Stand-Up Comedians’ Discourse: Semantic Analysis.” The research uses GVTH to identify and classify relative sentences, examining their contributions to semantic clarity and literary sophistication. Restrictive clauses offer precise definitions essential for academic specificity, but non-restrictive clauses supply additional details that enhance the text. The findings underscore non-native English speakers’ difficulties regarding relative clauses, shaped by grammatical disparities between their original language and English. This research emphasizes the necessity of learning relative clause usage to fulfill the requirements of high-quality academic writing. The study presents instructional implications to improve Indonesian graduate students’ and teachers’ academic writing abilities, who face mounting pressure to publish in foreign publications. Subsequent studies may build upon these findings by examining relative clause utilization across a wider corpus of academic literature and fields.